STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN PELAYANAN ADMINISTRASI DI MADRASAH TSANAWIYAH NEGERI 15 JOMBANG - Zidhan Danu Saputra; Abdullah Aminuddin Aziz (STKIP Pesisir Selatan, 2026)
Objective: This study aims to describe the implementation of human resource management (HRM) strategies at MTsN 15 Jombang, examine the condition of administrative services, and analyze the contribution of HRM strategies in improving administrative service quality. Methods: This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation. Participants included the principal, head of administration, vice principal for facilities, and administrative staff. Data were analyzed using the Miles and Huberman interactive model. Data validity was ensured through source and technique triangulation. Results: HRM strategies at MTsN 15 Jombang operate through five channels: needs-based workforce mapping via job analysis, competency-matched staff placement, digital capacity building through MOOC Pintar, performance oversight via SKP and E-Kinerja platforms, and multilevel employee motivation programs. These channels reduced service turnaround from 2-3 workdays to 1-2 hours, lifted procedural adherence from 72% to 91%, and achieved over 85% favorable user ratings via PTSP digital feedback. Novelty: This study presents an integrated six-component HRM model unifying workforce mapping, competency-based placement, capability building, performance governance, motivational leadership, and digital service delivery into one coherent framework for Islamic educational administration.